Causes Of The Phenomenon Of Homeless Children (Field Study) In The City Of Baquba - Jalil Ismael, Dunya (Opción, 2019)
The current research aims to identify the underlying causes of the phenome- non of displaced children. To achieve this goal, the researchers applied a meas- ure that included 15 paragraphs to identify the main causes of displacement on a sample of 100 children from the city of Baquba, distributed over four intersections in the city. The study reached the following results: The main reasons that led to the displacement of children are: 1-loss of both parents or one and not embrace the child by his family. 2-Family disintegration (aban- donment / divorce / family differences). 3-Poverty and low material level of the family and its inability to meet the needs of its children. 4-Addiction to the father of drugs and neglect of his family and deprive them of a stable and quiet life. 5-The head of the unemployed family and his attempt to send his children to the street to bring money in any way. 6-Domestic violence and abuse of par- ents of children such as beatings, insults and insults. 7 - The failure of school- ing and abuse of children by teachers in addition to the ignorance of parents. 8-Migration from the countryside to the city & a random housing in shanty- towns & outlying areas. 9-Mix the child with bad companions and share them, which lead the child to acquire the worst and ugliest acts because of poor control and indifference by the family or excess confidence with no one who understands and appreciates his feelings.